Analisis Kemampuan Berpikir Kritis Mahasiswa Dalam Menyelesaikan Masalah Geometri - Firdaus Firdaus (Universitas Negeri Makassar, 2022)
: One of the essential skills for university students is their ability to think critically in solving mathematical problems. This study aims to analyze the students’ critical thinking ability in solving mathematical problems on the topic of geometry. The sample consisted of 25 students. Written tests and in-depth interviews were administered to research participants. The results of tests and interviews were qualitatively analyzed to describe university students’ critical thinking skills using the indicators of the Leveling of Critical Thinking Abilities (LCTA), namely LCTA-0, LCTA-1, LCTA-2, and LCTA-3. The results showed that 0% of students at the LCTA-0 level, 60% at the LCTA-1 level, 28% at the LCTA-2 level, and 12% at the LCTA-3 level. This study reveals that students’ lack of interaction with complex mathematical problems limits students’ critical thinking ability. Therefore, it is suggested that educators need to give more complex problems to develop students’ critical thinking ability.